2004
DOI: 10.1103/physrevb.70.045407
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic properties of MgO nanotube clusters

Abstract: Finite magnesium oxide nanotubes are investigated. Stacks of four parallel squares, hexagons, octagons, and decagons are constructed and studied by the pseudopotential density functional theory within the local-density approximation. Optimized structures are slightly distorted stacks of polygons. These clusters are insulators and the band gap of 8.5 eV is constant over an investigated range of the diameters of stacked polygonal rings. Using the L"owdin population analysis a charge transfer towards the oxygen a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…It is gratifying to note that experimental observations of mass spectra [14,15,48,55] indicate the existence and stabilities of such stacked hexagonal rings, at least for small gas-phase clusters of MgO. Other experimental and theoretical [22,23,56] studies also provide evidence for the existence and stabilities of MgO nanotubes.…”
Section: Discussionmentioning
confidence: 93%
“…It is gratifying to note that experimental observations of mass spectra [14,15,48,55] indicate the existence and stabilities of such stacked hexagonal rings, at least for small gas-phase clusters of MgO. Other experimental and theoretical [22,23,56] studies also provide evidence for the existence and stabilities of MgO nanotubes.…”
Section: Discussionmentioning
confidence: 93%
“…One is by starting from the low-energy isomers of (ZnS) n [18][19][20][21][22][23][24], (BeO) n [30], (MgO) n [41][42][43][44][45][46][47][48][49][50][51] and (AuSR) n [17] clusters as reported in literatures. The other is by unbiased global search by the combination of genetic algorithm (GA) and DFT method, which has been successfully applied in the structural prediction of a number 5 of systems [30,[56][57][58][59][60][61].…”
Section: Computational Detailsmentioning
confidence: 99%
“…For (BeO) n clusters, the global minimum (GM) structures are rings to n = 5, double rings at n = 6 and 7, and cages at n ≥ 8 [30]. For (MgO) n [41][42][43][44][45][46][47][48][49][50][51], (TiO) n [52] and (BaO) n clusters [53] , the structures are preferred over the cubic-like ones. Puente and Aguado [44] showed that the interpretation of the magic numbers of small (MgO) n clusters in terms of stacking small (MgO) 3 subunits is cube.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been several theoretical studies on structural, electronic and adsorption properties of the MgO nanotube [37][38][39][40][41][42][43][44]. In our previous work [45,46], we had observed that the reactive (MgO) 12 species is not a cubic bulk-like structure, but a nanotube.…”
Section: Introductionmentioning
confidence: 96%